Primorye State Art Gallery as the center of the Far East art space - Kats, L.M. (Искусство Евразии, 2020)
The article is devoted to the last decade of exposition and exhibition activity of the Primorye State Art Gallery. The focus is on art projects that have become the result of increasingly strong inter-Museum contacts: “guest”, exchange and joint exhibitions. They are born as a result of searches for interested partners and sponsors, agreements with the heads of various institutions at forums and seminars. The patronage of Central museums is of great importance: the State Hermitage Museum, the state Tretyakov Gallery, the State Russian Museum, and others. The Primorye State Art Gallery organizes international exhibitions in order to promote Far Eastern fine art in the countries of the Asia-Pacific region, to open new names for these territories in the artistic sphere of the region and the district. The experience of the the Primorye State Art Gallery can be useful for museum workers in the Far Eastern and Siberian regions, and the information obtained can become an incentive for establishing new inter-museum contacts. The Primorye State Art Gallery is a relatively young museum formed in 1966 on the basis of the art collection of the Primorsky Regional Museum of Local Lore (now the Museum of the History of the Far East named after V. K. Arsenyev). Over five and a half decades, the gallery's funds have grown immeasurably, and it has become a methodological center for art museums in the Far East: the State Hermitage Museum has held six master classes on restoration and conservation of works of art in the gallery, and specialists from the State Russian Museum have been conducting scientific and practical seminars for the Far Eastern Federal district in recent years here.